Pengembangan LKPD Geometri Berbasis Etnomatematika Pembuatan Batu Bata Merah untuk Siswa SMP - Nadzira, Rizki Ayu; Wahyuni, Fina Tri (Circle: Jurnal Pendidikan Matematika, 2025)
This research aims to develop geometry LKPD teaching materials based on the ethnomathematics of making red bricks in Kebonalas Hamlet, Kudus Regency on building material with flat sided blocks for class VIII SMP students. The research uses the Research and Development (RnD) method with the 4D development model (Define, Design, Develop, and Disseminate). Data collection techniques include observation sheets, interviews, validation, student response questionnaires, and documentation. The research subjects were small scale trials with 6 students and large scale trials with 20 class VIII students at SMP N 2 Gebog. The research results show that the process of developing LKPD begins with observing problems and formulating learning objectives, followed by designing LKPD according to students' needs. The next stage is the creation and development of the LKPD which involves validation by experts, product revisions, and trials to determine the practicality of the product. The final stage is the distribution of products that are declared valid and practical. The ethnomathematics-based LKPD for making red bricks on the geometry of flat-sided block shapes is very valid and very practical for use in mathematics learning. Material expert validation obtained a percentage of 93.50% (very valid), media expert validation 86.67% (very valid), and student response questionnaire 93.00% (very valid). Small scale trials showed a percentage of 91.78% (very practical), while large scale trials were 89.40% (very practical). Thus, this LKPD is suitable for use as a mathematics teaching medium in class VIII SMP N 2 Gebog.